Towards the determination of driving factors of varying LST-LCZ relationships – a case study over 25 cities - Gholami Rostam, Mehdi; Beck, Christoph (Geographica Pannonica, 2019)
The current study aimed to prove the existence of a significant relation between land surface temperature (LST) and local climate zones (LCZs) and its possibility to be generalized to all cities around the world with different climatic zones and characteristics. The further step in this regard was to find the effective climatic and geographical variables affecting this potential relation. For that, 25 cities all around the world with various climatic conditions were selected based on the availability of appropriate satellite images and level zero data on the World Urban Database and Portal Tool (WUDAPT). After acquiring both LST and LCZ maps the comparison between them was made with the Wilcoxon rank sum test indicating the existence of any meaningful pattern. Then, 8 climatic and geographical variables and all possible combinations thereof were assessed to determine the effective drivers on the LST-LCZ relationship. The results showed that the combination of the latitude, mean and maximum annual temperature affected this connection more than any other considered variables.
Keywords: Land Surface Temperature (LST); Local Climate Zones (LCZs); Wilcoxon rank sum test; Hierarchical cluster analysis